AKI after pediatric cardiac surgery for congenital heart diseases–recent developments in diagnostic criteria and early diagnosis by biomarkers- - Toda, Yuichiro (J Intensive Care, 2017)
BACKGROUND: Acute kidney injury (AKI) after cardiac surgery in children with congenital heart disease is a common complication. AKI is also associated with high morbidity and mortality. The Kidney Diseases Improving Global Outcomes (KDIGO) criteria for AKI classification are now widely used for the definition of AKI. It is noteworthy that a statement about children was added to the criteria. Many studies aimed at finding useful biomarkers are now being performed by using these criteria. Clinicians should be aware of the recent progress in understanding AKI in children. MAIN CONTENTS: Unlike adult patients, young age is one of the major risk factors for AKI in pediatric cardiac surgery. The mechanism of the development of AKI in children might be different from that in adults because the surgical procedure and CPB technique in pediatric patients are greatly different from those in adult patients. There are many biomarkers for early detection of AKI, and some of them are widely used in hospitals. One of the major benefits of such biomarkers is the rapidness of expression for detecting increases in their expression levels. Neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, cystatin C, and albumin have been investigated in some studies, and the usefulness of these biomarkers for detection of AKI and diagnosis of disease severity has been shown. Although there are many interventions for preventing and treating AKI after cardiac surgery in children, there is still no specific effective treatment. Peritoneal dialysis is effective for only maintaining a negative fluid balance early after cardiac surgery. The long-term prognosis of AKI is an issue of interest. Although mortality and morbidity of AKI in the acute phase of disease remain high, the long-term condition in pediatric patients is relatively acceptable unlike in adults. CONCLUSIONS: KDIGO criteria are advocated as a diagnostic tool for common perception. Early recognition and intervention for AKI can be achieved by using several biomarkers. Further studies are needed to establish effective treatment for AKI.